EFFECT OF DIFFERENT ROOTSTOCKS ON POLLEN FERTILITY OF INTERSPECIFIC EGGPLANT HYBRID (SOLANUM MELONGENA L. X SOLANUM TORVUM SW.) GENOTYPES - A. Dayan; S. Çürük (Journal of Animal and Plant Sciences, 2022)
The major bottleneck in interspecific hybridization is the sterility of the hybrid individuals. Different methods such as tissue culture techniques, molecular studies and grafting are used to overcome the sterility barriers as a result of hybridization between species. In the present study, the grafting method was used to overcome the low pollen fertility of hybrid plants obtained from the hybridization between Solanum melongena and Solanum torvum. Three different rootstocks with high fertility (Pala, Faselis F1, and S. torvum) were used for grafting. Three interspecific hybrids (8/I-3, 8/II-1 and 8/IV-2) were used as the scion. Pollen viability and pollen germination rates of these genotypes were determined. According to the data obtained, it was determined that the pollen viability and germination were affected significantly by the rootstock-genotype combination. The highest rate of pollen viability and pollen germination was obtained from Pala - 8/II-1 combination. The rate of pollen stained in "red + pink" of the 8/II-1 genotype grafted on Pala rootstock increased 98.00 times and the pollen ratio stained only in red increased 77.87 times, compared to the non-grafted. The Pala was determined as the most suitable rootstock for the interspecific hybrids.
Keywords: Grafting; pollen fertility; rootstock; Solanum melongena; Solanum torvum